New species and records of quill mites of the family Syringophilidae (Acari: Prostigmata) from the passerines (Aves: Passeriformes) from the Russian Far East - Skoracki, Maciej; Mironov, Sergey V. (Zootaxa, 2013)
Two new species, Syringophilopisis pari sp. nov. from Poecile palustris Linnaeus (Paridae) and Torotrogla volgini sp. nov. from Emberiza elegans Temminck (Emberizidae) are described. Additionally, new host species are reported for three syringophilid species: Emberiza tristrami Swinhoe and E. rutila Pallas for Betasyringophiloidus schoeniclus (Skoracki); Sitta europaea Linnaeus (Sittidae) for Syringophilopsis sittae Skoracki et al., and Zosterops erythropleurus Swinhoe (Zos-teropidae) for Neoaulonastus zosterops Skoracki et al. All avian hosts were captured in the Primorsky Krai, Russia. The syringophilid fauna presently recorded from Russia is summarized.  n-ȷ5%'>20 in 2 species. The decrease in autosome number (14A) has been accompanied by 2 pairs of extremely large autosomes (Anoplocnemis binotata Distant and Cletus borealis Blöte) and the increase in autosome number (22A, 24A) has been accompanied by distinctly small autosomes (Petalocnemis obscura and Prionolomia sp.) in the complement. The behavior of chromosomes during meiosis is typical of Coreidae. Deviations wherever recorded are discussed. During diplotene, chiasmata are located terminally and there is a predominance of a single chiasma per bivalent. However, in Anoplocnemis binotata and Cletus borealis, one or both of the large bivalents show two terminal or subterminal chiasmata in diplotene. A regular arrangement of chromosomes is observed during both metaphase I and II: all the autosomes form a ring with microchromosomes lying inside and sex chromosomes lying outside the ring.